Stylization and language ideologies in Pidgin comedic skits. (June 2018) - Furukawa, Gavin
Abstract: Hawaiʻi Creole or Pidgin is a highly stigmatized language variety spoken by half a million people in the state of Hawaiʻi. The residents of Hawaiʻi and speakers of this language often view it with a complex mixture of both hate and love. Previous discursive approaches to this topic have often focused on the strategic, pragmatic uses of the language for constructing identities and ideologies however the complex and often contradictory nature of Pidgin speakers' beliefs and attitudes towards their language is often missing from these analyses. In this article, the ideologies of Pidgin are examined through analyzing the comedic skits of Rap Reiplinger, a local comedian whose work still enjoys great popularity over 30 years after his death. By mapping out the indexical fields this article shows how multiple and sometimes opposing ideologies may be simultaneously produced and reproduced in Pidgin comedy routines by the formation of multiple semiotic centers. The analysis will also show how these ideologies are then re-appropriated by others through selective activation of these indexical fields and how the activation of multiple fields can lead to the reproduction of those contradicting beliefs that are at the core of Pidgin speakers attitudes towards their own language.